Genetic diversity of near genome-wide hepatitis C virus sequences during chronic infection: evidence for protein structural conservation over time. - Hui Li; Austin L Hughes; Nazneen Bano; Susan McArdle; Stephen Livingston; Heike Deubner; Brian J McMahon; Lisa Townshend-Bulson; Rachel McMahan; Hugo R Rosen; David R Gretch (PLoS ONE, 2011)
Infection with hepatitis C virus (HCV) is one of the leading causes of chronic hepatitis, liver cirrhosis and end-stage liver disease worldwide. The genetics of HCV infection in humans and the disease course of chronic hepatitis C are both remarkably variable. Although the response to interferon treatment is largely dependent on HCV genotypes, whether or not a relationship exists between HCV genome variability and clinical course of hepatitis C disease still remains unknown. To more thoroughly understand HCV genome evolution over time in association with disease course, near genome-wide HCV genomes present in 9 chronically infected participants over 83 total study years were sequenced. Overall, within HCV genomes, the number of synonymous substitutions per synonymous site (d(S)) significantly exceeded the number of non-synonymous substitutions per site (d(N)). Although both d(S) and d(N) significantly increased with duration of chronic infection, there was a highly significant decrease in d(N)/d(S) ratio in HCV genomes over time. These results indicate that purifying selection acted to conserve viral protein structure despite persistence of high level of nucleotide mutagenesis inherent to HCV replication. Based on liver biopsy fibrosis scores, HCV genomes from participants with advanced fibrosis had significantly greater d(S) values and lower d(N)/d(S) ratios compared to participants with mild liver disease. Over time, viral genomes from participants with mild disease had significantly greater annual changes in d(N), along with higher d(N)/d(S) ratios, compared to participants with advanced fibrosis. Yearly amino acid variations in the HCV p7, NS2, NS3 and NS5B genes were all significantly lower in participants with severe versus mild disease, suggesting possible pathogenic importance of protein structural conservation for these viral gene products.